The effect of a 5-week therapeutic massage on erector spinae and upper trapezius muscle stiffness as determined by shear-wave elastography: a randomized controlled trial - Jelen, Amadej; Javornik, Erina; Meh, Sara Gloria; Kozinc, Žiga (Frontiers in Sports and Active Living, 2024)
Introduction Massage is an effective treatment for reducing pain, swelling, stiffness, and improving muscle mobility. Although self-reported benefits on muscle stiffness and pain are well-known, studies measuring muscle stiffness objectively are scarce. Methods A randomized controlled trial involving 30 recreationally active young women (22.3 ± 0.4 years) was conducted. The participants were randomly assigned to either the control group or the intervention group which received a series of five 30-min whole back therapeutic massage sessions over 5 weeks. Shear wave elastography was used to assess muscle stiffness (erector spinae (ESp) and upper trapezius (UT) muscles) before and after the intervention and at 3-week follow-up. Results For ESp, there was no statistically significant time × group interaction (F = 2.908; p = 0.063). However, there was a statistically significant and large time × group interaction for UT (F = 13.533; p = 0.006; η2 = 0.19). Post-hoc testing for time indicated that the shear modulus in the intervention group was reduced at follow-up (p = 0.005; d = 1.02), while the difference between baseline and post-intervention measurements were not statistically significant (p = 0.053; d = 0.75). Conclusion In conclusion, massage significantly reduced proximal UT stiffness both 3 days and 3 weeks after the intervention. However, it had no significant effect on the distal part of UT or the ESp muscle.